Anti-inflammatory activity of propolis extracts: a review - Almeida, E. C. De; Menezes, H. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2002)
Since primeval times, the inflammatory process has been described in many different ways. Several anti-inflammatory therapies have been used in different biological models. However, in a recent back to nature move, modern man is searching for natural products with medicinal properties, particularly those obtained from plants and bees. Propolis has been used in folk medicine for a very long time. The many compounds present in propolis require investigation.Physical-chemical analysis studies have not sufficiently established quality standards of propolis containing products. These standards should depend especially on their different pharmacological activities. There are few studies reporting on the in vitro anti-inflammatory activity of propolis containing products. It is necessary to evaluate the anti-inflammatory potential of commercial products containing propolis.
Keywords: propolis; anti-inflammatory activity; bees; Apis mellifera; natural products